The Role of Work Motivation in Mediation of Leadership Style on Employee Performance (a Literaruter Study Human Resource Management) - Oktarini Oktarini (Dinasti Publisher, 2023)
Previous research or relevant research is very crucial in research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomena of the relationship or the influence between variables. This article reviews the role of motivation in mediating leadership style on employee performance, A Human Resource Management Literature Study. The results of this research library are that: 1) leadership style affects employee motivation; 2) leadership style affects employee performance; 3) work motivation affects employee performance, and 4) leadership style through work motivation affects employee performance.